Association of Telehealth Encounters With Lung Cancer Screening Consultation in the U.S.: Preliminary Results - Zhigang Xie, PhD, BMed, MPA; Sericea Stallings-Smith, DrPH, MPH; Beomyoung Cho, PhD, MPH; Jennifer Wells, BA; Young-Rock Hong, PhD, MPH (AJPM Focus)
Introduction: To promote lung cancer screening among the eligible population, a crucial step involves a shared decision-making discussion between the patient and primary care provider regarding lung cancer screening services. Little is known whether telehealth visits can be deemed comparable with in-person visits for lung cancer screening consultations. Methods: This study used data from the 2022 Health Information National Trends Survey 6. Multivariable logistic regression models were employed to examine differences in lung cancer screening consultations between telehealth users and nonusers, adjusting for selected covariates. Results: Overall, 41.2% had used telehealth at least 1 time in the past 12 months, and 9.9% had lung cancer screening consultations with their healthcare providers at least 1 time. There was no statistically significant difference in the odds of lung cancer screening consultations with healthcare providers between telehealth users and nonusers (AOR=0.91; 95% CI=0.36, 2.29). Of telehealth users, the odds of lung cancer screening consultations among exclusive phone call users (AOR=1.20; 95% CI=0.23, 6.17) and both video and phone call users (AOR=0.82; 95% CI=0.11, 5.98) were not statistically different from that among exclusive video call users. Conclusions: Despite the overall low rate of patient–provider lung cancer screening consultations in eligible individuals, this study suggests that telehealth and in-person encounters seem to be comparable for lung cancer screening consultations.